2010
DOI: 10.1016/j.rbmo.2010.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture on the day of embryo transfer: a randomized controlled trial of 635 patients

Abstract: This prospective, randomized, controlled and double-blinded trial studied whether acupuncture in relation to embryo transfer could increase the ongoing pregnancy rates and live birth rates in women undergoing assisted reproductive therapy. A total of 635 patients undergoing IVF or intracytoplasmic sperm injection (ICSI) were included. In 314 patients, embryo transfer was accompanied by acupuncture according to the principles of traditional Chinese medicine. In the control group, 321 patients received placebo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 16 publications
(33 reference statements)
0
109
1
1
Order By: Relevance
“…There were 14 RCTs (n = 3,971) performing only around the time of ET. The quality of the included trials is summarized in table 1; 7 of the 14 studies were published as full reports [17,18,19,20,21,22,23], while the remaining 7 were published as conference abstracts [10,11,24,25,26,27,28]; 4 of the studies were in Europe (2 in Denmark [17,18], 1 in Brazil [11], 1 in Germany [20]), 3 in China [21,22,23] and 7 in the USA [10,18,19,24,25,26,27]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 14 RCTs (n = 3,971) performing only around the time of ET. The quality of the included trials is summarized in table 1; 7 of the 14 studies were published as full reports [17,18,19,20,21,22,23], while the remaining 7 were published as conference abstracts [10,11,24,25,26,27,28]; 4 of the studies were in Europe (2 in Denmark [17,18], 1 in Brazil [11], 1 in Germany [20]), 3 in China [21,22,23] and 7 in the USA [10,18,19,24,25,26,27]. …”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 trials, 7 performed sham (placebo) acupuncture in the control group; 2 trials [23,25] belonged to the unblinded trials group and 5 [17,19,21,26,27] belonged to the group of trials that were blinded to the physicians. Of the above 5 trials, all except the study of Paulus et al [27] were double-blind trials.…”
Section: Resultsmentioning
confidence: 99%
“…However, several recent publications contradicted previous findings. Andersen et al (9) applied verum or placebo acupuncture on the day of ET in 635 patients and found no difference of PR in the two groups. There were also reports showing that acupuncture has only a placebo effect, yet they confirmed that acupuncture was safe for women undergoing ET (10,11).…”
mentioning
confidence: 99%
“…Diese randomisierte kontrollierte Studie (RCT) zeigte eine signifikante Verbesserung der Schwangerschaftsrate (SR) bei Patientinnen mit Akupunkturbehandlungen kurz vor und nach dem Embryotransfer (ET) [12]. In einigen der darauffolgenden RCTs konnte der günstige Einfluss von Akupunktur auf die SR bestätigt werden [14,15], während in anderen keine signifikanten Unterschiede zwischen der Akupunktur-und der Kontrollgruppe [16][17][18][19][20][21][22], und zum Teil eine signifikant höhere SR in der Kontrollgruppe [23,24] …”
Section: Modalities Of Acupuncture Treatments In Assisted Reproductivunclassified